ADAPTIVE DEFECTOSCOPY OF THE HIDDEN SURFACES OF CASTINGS AND ROLLING - E. I. Marukovich; E. M. Patuk; A. P. Markov; E. V. Efimenko; O. Yu. Bondarev (Литьë и металлургия)
Ways and structures of information and technological assessment of surfaces sate in nooks of castings and rolling are considered.